2006
DOI: 10.1158/1078-0432.ccr-05-0835
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Lymph Node Metastasis in Patients with Endometrioid Endometrial Cancer Using Expression Microarray

Abstract: Purpose: To characterize the gene expression profiles of endometrioid endometrial cancers associated with lymph node metastasis in an effort to identify genes associated with metastatic spread. Experimental Design: Tumors from 41 patients with endometrioid endometrial cancer grossly confined to the uterine cavity were evaluated. Positive lymph nodes were noted in 12 of 41 patients. RNA was analyzed for gene expression using the Affymetrix HG133A and HG133B GeneChip set, representing 45,000 array features cover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…7A). Furthermore, enrichment of metastatic gene signatures in other cancer types (Bidus et al 2006;Rickman et al 2008) was also found in control versus hnRNPM knockdown cells (Supplemental Fig. S7).…”
Section: Molecular Classification Of Breast Cancers Divides Them Intomentioning
confidence: 79%
“…7A). Furthermore, enrichment of metastatic gene signatures in other cancer types (Bidus et al 2006;Rickman et al 2008) was also found in control versus hnRNPM knockdown cells (Supplemental Fig. S7).…”
Section: Molecular Classification Of Breast Cancers Divides Them Intomentioning
confidence: 79%
“…Human mutations in ZIC family members determine many clinically significant congenital abnormalities (54). Moreover, aberrant expression of ZIC2 has been observed in medulloblastomas (55), small cell lung cancers (56), endometrial cancer with node metastasis (57) and in bladder, colon and breast cancer (56). OGFRL1 encodes the opioid growth factor receptor-like 1, whose biological function is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Caveolin-2 is positively correlated with tumour grade and squamous features of urothelial carcinoma (Fong et al, 2003) and it forms hetero-oligomeric complexes with Caveolin-1, that are correlated to disease progression and metastasis in human prostate cancer (Thompson et al, 1999). PTTG1 is a novel oncogene that may serve as a prognostic marker for tumour invasiveness and metastasis (Ramaswamy et al, 2003), and MAD2L1 has been associated with lymph node metastasis of several cancer types (Bidus et al, 2006). THBS1 was the gene most correlated with E2F3 knockdown; it has been linked to Abbreviation: MHC, major histocompatibility complex.…”
Section: Role Of E2f3 Expression In Human Bladder and Prostate Cancermentioning
confidence: 99%